ANALYSIS OF ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS’ CREATIVITY IN CHANGING SONGS INTO SIGN LANGUAGES - Sri Hardiningsih; Muh. Rijulul Akbar; Sholihin Sholihin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
Education for Children with Special Needs (PABK) is an optional course in the Elementary School Teacher Education Students (PGSD) study program where in this course, there is a hearing difficulty (deaf). One of the strategies that prospective educators (in this case students) can do is to prepare themselves when later adapting to children who have hearing impairments. The strategy that can be done in dealing with children with hearing difficulties (deaf) in elementary school is to use sign language. So that the need for students to be trained at least to be able to use simple sign language. So, students are directed to be able to compose songs into sign language. The type of this research is a quantitative descriptive study that aims to determine the creativity of students in composing songs into sign language as one of the strategies in dealing with children with special needs hearing impairments. The subjects in this study were students who were selected based on purposive sampling with the criteria desired by the researcher. This research was conducted by filling in the instruments that had been validated by expert judgment. The results showed that in general, students were able to compose songs into sign language. Based on these results, it can be concluded: that the test results assessed from the research instrument, students were able to compose songs into sign language quite well, this is shown in the results where 77% with a score of 59-69 with a total of 11 students were able to compose songs into sign language. Meanwhile, 23% with a score of 70-80 with a total of 4 students were able to compose songs into sign language well.